1976
DOI: 10.1038/bjc.1976.160
|View full text |Cite
|
Sign up to set email alerts
|

Solid tumour models for the assessment of different treatment modalities: IV. the combined effects of radiation and 5-fluorouracil

Abstract: Summary.-Neither radiation alone (375 to 1500 rad) nor 5 -fluorouracil (FU) alone (50-250 mg/kg) is sufficient to prevent an increase in the volume of the solid tumour model hepatoma 3924A. However, as little as 750 rad with 100 mg/kg FU can reduce the tumour below the volume at the time of treatment for as long as 14 days. A series of combined FU and radiation doses given every 11 days should then result in successively smaller tumour volumes until the tumour is eradicated.Changes in tumour volume were analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1977
1977
1997
1997

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Fractionation over the 3-or 5-day period prevents marrow recovery within the time necessary for animal survival. This delay in recovery increased the mortality rates from 10% in the large single-dose FU group to 60% for the 3 daily fractionated groups and 80% for the 5 The in vitro studies by Wolberg and Ansfield (1971) (Looney, et al, 1976b, c). In these experiments, the marrow recovery time after a single 50 mg/kg dose of FU is 7-8 days.…”
Section: Discussionmentioning
confidence: 92%
“…Fractionation over the 3-or 5-day period prevents marrow recovery within the time necessary for animal survival. This delay in recovery increased the mortality rates from 10% in the large single-dose FU group to 60% for the 3 daily fractionated groups and 80% for the 5 The in vitro studies by Wolberg and Ansfield (1971) (Looney, et al, 1976b, c). In these experiments, the marrow recovery time after a single 50 mg/kg dose of FU is 7-8 days.…”
Section: Discussionmentioning
confidence: 92%
“…Previous reports from these studies (1)(2)(3)(4)(5)(6) have demonstrated that recovery from the effects of a large dose of 5-fluorouracil (5-FUra) in rats occurs 10-11 days after treatment. The maximal rate of tumor volume change occurs 12 days after 5-FUra (4).…”
mentioning
confidence: 99%
“…Studies on the solid tumor model hepatoma 3924A indicated that neither radiation alone [375-1500 roentgens (0.10-0.38 C/kg)] nor 5-FUra alone (50-250 mg/kg) would control tumor growth. However, these results suggested that radiation in combination with 5-FUra treatment could in principle transform the management of a chemotherapeutically resistant solid tumor from an untreatable situation to a treatable situation by the combined modality treatment every 11 days until the tumor is eradicated (2).…”
mentioning
confidence: 99%